PECORARO, Rosario Rossano - La filosofia del voyeur. Estasi e scrittura in Emile Cioran . Eclitrice Il Sapere. Via Roma, 210 - 84121 - Salermo (Itália). - Pecoraro, Rossano (Veritas (Porto Alegre), 2000)
Resenha da obra.